Sosialisasi dan Edukasi Tumbuhan Nibung Sebagai Maskot Flora Propinsi Riau di SMAN 1 Kabupaten Bengkalis - Desti, Desti; Aisyah, Baiq Nurul; Nafsiah, Izzatul (UIR Press, 2019)
The activities of the community aims to support the efforts to conservation efforts the nibung plant as a flora mascot in Riau province in SMAN 1 Bengkalis Regency. This activity is carried out to provide information to the community and increase public awareness in the effort to conserve nibung plants in the future, especially for students at SMAN 1 Bengkalis Regency, Riau. The activity was carried out with the dissemination and education of the nibung plants as the flora mascot of Riau Province. The implementation of actions in this activity is by providing material about the description of the nibung plant. Based on the activities that have been carried out, it is found that students in SMAN 1 Bengkalis Regency generally know nibung plants and often find and use them in their daily lives. However, most students do not yet know that the Nibung plant (Oncosperma tigillarium) is the mascot of Riau Province. During the implementation of community service activities, the students were very enthusiastic and actively participated in the activity while participating in the activity, and stated that that activity was very effective in increasing students' understanding of the Riau flora mascot and its conservation efforts.